Investigation on the Stabilizing Effect of Titanium in HfO2-Based Resistive Switching Devices With Tungsten Electrode - Fra, Vittorio; Shahrabi, Elmira; Leblebici, Yusuf; Ricciardi, Carlo (Frontiers in Nanotechnology, 2020)
Resistive switching (RS) devices, also referred to as Resistive Random Access Memories (ReRAMs), rely on a working principle based on the change of electrical resistance following proper external electrical stimuli. Since the demonstration of the first resistive memory based on a binary transition metal oxide (TMO) enclosed in a Metal-Insulator-Metal (MIM) structure, this class of devices has been considered a key player for simple and low-cost memories. However, successful large-scale integration with standard CMOS technologies still needs systematic investigations. In this work, we examine the beneficial effect titanium has when employed as buffer layer between CMOS-compatible materials like hafnium dioxide and tungsten. Hindering the tungsten oxidation, Ti provides RS stabilization and allows to get faster responses from the devices. Through an extensive comparative study, the effect of both thickness and composition of Ti-based buffer layers is investigated. The reported results show how titanium can be effectively employed to stabilize and tailor the RS behaviour of the devices, and they may open the way to the definition of new design rules for ReRAM-CMOS integration. Moreover, the gradual switching and the response speed tunability observed employing titanium might also extend the domain of interest of these results to brain-inspired computing applications.